Changes in properties of a newly cleared tropical Alfisol as affected by mulching - Lal, R.; De Vleeschauwer, D.; Nganje, R.M. (1980)
Rapid deterioration in soil physical properties following deforestation for arable land use adversely affects crop production from soils in the humid and subhumid tropics. This investigation was conducted to determine whether the rate of deterioration can be minimized by the use of crop residue mulches. Changes in soil properties of a newly cleared tropical Alfisol resulting from mulch rates of 0, 2, 4, 6, and 12 tons ha−1 season−1 of rice (Oryza sativa) straw were investigated from 1976 to 1977. Total porosity, 18 months after initiating the experiment, was 48, 50, 55, 55, and 59%, respectively, for increasing mulch rate. Similarly affected were relative proportions of macropores, saturated hydraulic conductivities, field infiltration rates, and moisture retention at 0.1 and 0.3 bar suctions. Decrease in the maximum temperature was 3.3, 4.1, 4.5, and 5.4°C for 2, 4, 6, and 12 ton/ha mulch rates respectively, compared with the unmulched control. The water runoff was 18, 10, 4, 1, and 0% of the rainfall received for increasing mulch rates, respectively. The chemical fertility of the soil decreased with time after forest removal. However, the rate of degradation was less with increasing mulch rate. The rate of decline of organic matter content over the 18-month period was 0.103, 0.100, 0.092, 0.083, and 0.078% per month for 0, 2, 4, 6 and 12 tons/ha of mulch, respectively.